Analisis Penyebab, Konsekuensi, dan Solusi Potret Investasi di Indonesia Pasca Reformasi - Melinda Wirastiti; Aditya Arga Widhyasa; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Investment in Indonesia is the main guideline in increasing economic productivity. This research aims to explain the causes, consequences, solutions and conditions of investment in post-reformation Indonesia. This research will examine the factors that influence investment, the impact of investment on the economy and labor market, as well as solutions to improve the investment climate and overcome existing obstacles. not only explains conditions but also explains the role of investment in economic growth, as well as obstacles to economic growth.